Analysis Of Coastal Women’s Dual Roles In Ternate City - Misrina Misrina; Muhammad Arif Wicaksono (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to analyze the coastal women’s dual roles in Ternate City and its impact on their physical and mental well-being. This study used a qualitative approach to identify the division of work between domestic roles and productive roles, factors affecting dual roles, and their impact on women's well-being. The research method involved literature study, observation, and secondary data analysis. The results of the study showed that coastal women experienced significant dual roles due to patriarchal cultural norms, unequal access to resources, and economic pressures. The impacts covered sleep disturbances, physical fatigue, stress, anxiety, and depression. Efforts such as strengthening inclusive development programs, changing cultural norms, and developing work flexibility policies that consider women's dual roles are needed to reduce double workload.